Molecular, morphological, and anatomical data support a new species of Croton sect. Geiseleria (Crotonoideae, Euphorbiaceae) - Sodre, Rodolfo C. [UNESP]; Souza, Alessandro O. de; Alonso, Alexandre A.; Silva, Marcos J. da (Springer, 2019)
Croton macrosepalus Sodre & M.J.Silva(sp. nov.), a new species found in the states of Bahia, Goias, and Tocantins, in Brazil, is described and illustrated. Although it is morphologically similar to Croton spica, the novel species can be differentiated from it by having large glandular stipules, entire or sometimes serrulate leaf margins, petioles with 2-8 cylindrical nectary glands at the apex, ovate pistillate sepals, and a hat-shaped caruncle. The habitat, conservation status, phenology, and morphological relationships of the species are also discussed. Morphological data and molecular analyses using ITS and trnL-trnF support the placement of C. macrosepalus and C. spica in Croton sect. Geiseleria. A geographic distribution map, images, notes about the leaf anatomy of both species, and their phylogenetic relationships are provided.
Keywords: Cerrado; Croton; Endemism; Phylogeny